Women's Psychiatry - Balta, G.; Dalla, C; Kokras, N (Adv Exp Med Biol, 2019)
Brain disorders and mental diseases, in particular, are common and considered as a top global health challenge for the twenty-first century. Interestingly, women suffer more frequently from mental disorders than men. Moreover, women may respond to psychotropic drugs differently than men, and, through their lifespan, they endure sex-orientated social stressors. In this chapter, we present how women may differ in the development and manifestation of mental health issues and how they differ from men in pharmacokinetics and pharmacodynamics. We discuss issues in clinical trials regarding women participation, issues in the use of psychotropic medications in pregnancy, and challenges that psychiatry faces as a result of the wider use of contraceptives, of childbearing at older age, and of menopause. Such issues, among others, demand further women-oriented psychiatric research that can improve the care for women during the course of their lives. Indeed, despite all these known sex differences, psychiatry for both men and women patients uses the same approach. Thereby, a modified paradigm for women's psychiatry, which takes into account all these differences, emerges as a necessity, and psychiatric research should take more vigorously into account sex differences.
Keywords: *Mental Disorders; *Psychiatry; *Reproductive Health; *Women's Health Services; Aged; Contraceptives; Female; Global Health; Humans; Male; menopause; Menopause/*psychology; Mental Health Services; pharmacodynamics; Pharmacokinetics; Pregnancy; Psychotropic Drugs/therapeutic use; Sex differences; Women; Women's Health